(untitled) (Research, Society and Development, 2022)
The aim of this paper is to discuss the process of the constitution of the Sustainable Development Goals and, by extension, present how the scientific community has been collaborating with its legitimization and adoption. Specifically, we will explore and contextualize the 2030 Agenda and its relationship with the scientific community, presenting an overview of the field, as well as providing recommendations and directions for future research. Methodologically, the manuscript shares an exploratory approach and is carried out through bibliographic reviews and bibliometric analysis. The main results found are: most of the published studies analyzed originate from North-Global countries; there has been a quantitative growth regarding the number of publications made in the period consulted, especially between the years 2019-2021; regarding the types of studies identified, case studies on experiences implemented in the university environment stand out, as well as studies that address the social commitment of this community in relation to the SDGs; as for research collaboration, there is a predominance among countries of the Global North, with sporadic collaborations between countries of the Global North-South and the Global South-South.